Antituberculosis Drug Induced Hepatitis: A Case- Report - Shah, Priyanshi R; Sajan, Cyril; Mistry, Mahek (Journal of Pharmacy Practice and Community Medicine)
Isoniazid, Rifampin and Pyrazinamide are first line antituberculosis medication. Among them isoniazid and pyrazinamide inhibit mycolic acid synthesis and rifampicin inhibit RNA polymerase. They are potent hepatotoxic. These drugs metabolize in liver by CYP450 enzyme. The drug toxicity is differing in different individuals because in some individuals drug metabolize by different pathway. Apart from hepatotoxicity, there are some reported cases of antituberculosis drug induced cutaneous reaction and gastrointestinal disturbances. A 31-year-old female patient came to respiratory department with complain of breathlessness, chest pain, abdominal pain, weight loss and loss of appetite. She was diagnosed with tuberculosis two months. For that she was put on HRZE regimen. Her laboratory data showed she had hepatitis. After stopping potent hepatotoxic medication her laboratory data started to normalize and symptoms relived. For tuberculosis she was shifted to alternative regimen. To prevent adverse drug reaction close monitoring of patient and therapy is required.
Keywords: Adverse drug reaction; Liver metabolism; Antituberculosis drugs; Hepatotoxic drugs; Liver injury; Cutaneous reaction